题目:若 (x>0,y>0) 且满足 (x+y=xy) ,则 (dfrac{1}{x-1}+dfrac{1}{y-1}) 的最小值为 (underline{qquadqquad}) .
方法一:
由 (x+y=xy) 得 (dfrac{1}{x}+dfrac{1}{y}=1) ,所以
[dfrac{1}{x-1}+dfrac{1}{y-1}=dfrac{x+y-2}{(x-1)(y-1)}=x+y-2=(x+y)(dfrac{1}{x}+dfrac{1}{y})-2=dfrac{y}{x}+dfrac{x}{y}geqslant 2
]
当且仅当 (x=y=2) 时,等号成立。
方法二:
令 (dfrac1x=sin^2 heta,dfrac1y=cos^2 heta) ,则
[dfrac{1}{x-1}+dfrac{1}{y-1}=dfrac{1}{dfrac{1}{sin^2 heta}-1}+dfrac{1}{dfrac{1}{cos^2 heta}-1}=dfrac{sin^2 heta}{cos^2 heta}+dfrac{cos^2 heta}{sin^2 heta}geqslant2
]
当且仅当 (sin^2 heta=cos^2 heta=dfrac12) 时,即 (x=y=2) 时,等号成立。
方法三:
令 (dfrac1x=dfrac12+t,dfrac1y=dfrac12-t) ,则 (x=dfrac{2}{1+2t}>0,y=dfrac{2}{1-2t}>0)
[dfrac{1}{x-1}+dfrac{1}{y-1}=dfrac{1}{dfrac2{1+2t}-1}+dfrac{1}{dfrac2{1-2t}-1}=dfrac{1+2t}{1-2t}+dfrac{1-2t}{1+2t}geqslant2
]
当且仅当 (1+2t=1-2t=dfrac12) 时,即 (x=y=2) 时,等号成立。